THE USE OF THE SHOW, DON’T TELL TECHNIQUE IN TEACHING WRITING OF DESCRIPTIVE TEXTS FOR SENIOR HIGH SCHOOLS STUDENTS - Fitri Ramadhani Lukman; Saunir Saun (Universitas Negeri Padang, 2016)
This paper is aimed to discuss about the use of The Show Don’t Tell technique which can develop students’ writing ability. In the beginning, the teacher explains the elements of descriptive text. Next, the theacher can use The Show Don’t Tell technique as an exercise to help the students develop ther writing ability.in this activity, the students will be divided into some groups which consist of ,at least, five students. After that, each group is asked to prepare the sheet that will be used to write after the teacher give a picture as a topic. The topic of each group will be different one and another. Next, each student in each group write a sentence which relates to the topic given. They will do this activity until the last member in each group. Before they submit the paper, the teacher asks them to check the correctness of their writing with their group. After applying this activity, it is hoped that students’ ability in writing descriptive text will increase and also can get their interest to write descriptive text easily because this activity is really fun.